Alpha-Synuclein Seed Amplification Assays in Parkinson’s Disease: A Systematic Review and Network Meta-Analysis - Jamir Pitton Rissardo; Ana Leticia Fornari Caprara (Clinics and Practice)
Introduction and objective: Assessment of α-synuclein (αSyn) seed amplification assays (αSyn-SAA) accuracy in distinguishing Parkinson’s disease (PD) from controls using cerebrospinal fluid (CSF), blood, skin, extracellular vesicles (ECV), saliva, olfactory mucosa (OM), gastrointestinal tract (GIT), and submandibular gland (SMG). Methodology: PubMed was searched for articles from 2010 to January 2025. The quality assessment used robvis. Diagnostic values with a 95% confidence interval (CI) were obtained. Z-test, Wald CI, and ANOVA were performed. Diagnostic odds ratio (DOR) was used. Results: αSyn-SAAs showed strong diagnostic performance in distinguishing PD from controls across various tissue and fluid types. Overall, αSyn-SAAs demonstrated high sensitivity (86%) and specificity (92%). Among all biomatrices, CSF, skin, blood, and ECV yielded the highest diagnostic accuracy, with sensitivity and specificity approaching or exceeding 90%. In contrast, saliva, oral mucosa, and gastrointestinal tract samples showed more modest sensitivity, though specificity remained relatively high. ECV, CSF, skin, and blood matrices also demonstrated the highest DOR, supporting their potential clinical utility. Conclusions: ECV and blood warrant priority in αSyn-SAA for high accuracy and minimal invasiveness, while GIT, OM, and oral samples show limited utility; saliva and SMG need refinement.